Effect of polypropylene fibers on concrete fire resistance - Shihada, Samir (Journal of Civil Engineering and Management, 2011)
The objective of this study is to investigate the impact of polypropylene fibers on fire resistance of concrete. In order to achieve this, concrete mixtures are prepared by using different percentages of polypropylene; 0%, 0.5% and 1%, by volume. The samples are heated to 200, 400 and 600 °C, for exposures up to 6 hours, and tested for compressive strength. Based on the results of the study, it is concluded that the relative compressive strengths of concretes containing PP fibers were higher than those of concretes without PP fibers. Furthermore, it can be concluded that concrete mixes which are prepared using 0.5% PP fibers, by volume, can significantly promote the residual compressive strength during the heating. Polipropireno pluoštoį taka betono atsparumui ugniai Santrauka. Tyrimo tikslas – išnagrinėti polipropireno pluošto įtaką betono atsparumui ugniai. Buvo gaminami betono mišiniai su 0 %, 0,5 % ir 1 % polipropireno dalimis. Bandiniai buvo kaitinami iki 200, 400 ir 600 °C, laikomi šiose temperatūrose 6 valandas ir bandomi nustatant gniuždomajį stiprį. Remiantis bandymų rezultatais daroma išvada, kad betono su polipropireno pluoštu stipris buvo didesnis už betono be šio priedo stiprį. Kita straipsnio išvada ta, kad betono mišiniai, kurių 0,5 % tūrio sudaro polipropireno pluoštas, leidžia labai padidinti liekamajį gniuždomajį įkaitinto betono stiprį. Reikšminiai žodžiai: polipropirenas, pluoštas, atsparumas ugniai, patogumas kloti, poveikis.